Chemotypic characterization of diversity in essential oil composition of Ocimum species and varieties from India. Issue 6 (2nd November 2018) - Raina, Archana P.; Gupta, Veena
ABSTRACT: Chemical composition of essential oils isolated from four species of Ocimum ( Ocimum basilicum L., Ocimum × citriodorum Vis., Ocimum kilimandscharicum Gurke, Ocimum. viride Willd.) and six botanical varieties of Ocimum basilicum L. ( O. basilicum var. difforme, O. basilicum var. purpurascens, O. basilicum var. basilicum, O. basilicum var. pilosum, O. basilicum var. glabratum and O. basilicum var. thyrsiflora ) were investigated by GC/FID and GC/MS. Results revealed a total of sixty-four volatile compounds showing both qualitative and quantitative variations among these species/varieties in distribution of compounds, chemical profiles and chemotypes. On the basis of chemical composition and hierarchical clustering, Ocimum species/varieties were classified into seven different chemotypes. Ocimum × citriodorum showed two different chemotypes rich in geranial/neral and methyl chavicol. O. kilimandscharicum showed camphor-rich chemotype (43.21%), while O. viride was found to be eugenol-rich chemotype (77.86%). Among the O. basilicum varieties, linalool-rich chemotype was identified in thyrsiflora, difforme, purpurascens and glabratum, whereas methyl chavicol-rich chemotype was found in pilosum . The most commonly found species of O. basilicum var. basilicum showed four chemotypes: linalool, methyl chavicol, (E)- methyl cinnamate and mixed type having both linalool and methyl chavicol. These essential oils of Ocimum with varying chemical compositions and chemotypes can be utilized in perfumery, pharmaceutical, food preservation and aromatherapy industries.